Tourism Revitalization In Indonesia - Fitri Mukarromah; Hendri Hermawan Adinugraha (IAIN Syekh Nurjati Cirebon, 2022)
One form of community empowerment in the village is the Tourism Village. Village development is the basis of national development. Each village is expected to be able to carry out development independently so that community welfare will be easily realized and increase the people's prosperity index. The policy of revitalizing tourism development has an impact on the development of beautiful and livable rural areas with natural resources and beautiful scenery which has become a trending topic on social media. The shift in tourist visits to the village is the reason for the revitalization of special tourism developments called tourist villages which are thick with cultural attractions and live together with residents. The development of tourist villages can add more diverse tourist attractions that can attract tourists, to increase community economic activities. Revitalization of tourism development as an alternative development approach that aims to increase economic growth, overcome unemployment, alleviate poverty, and improve people's welfare. Tourism can be used as a strategic medium in economic empowerment by providing opportunities for the community to develop and empower tourism. This research uses library research methods. The data sources used are primary data and secondary data.Keywords: tourism, revitalization, cultural